2010
DOI: 10.3201/eid1608.100196
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic (H1N1) 2009 Surveillance in Marginalized Populations, Tijuana, Mexico

Abstract: To detect early cases of pandemic (H1N1) 2009 infection, in 2009 we surveyed 303 persons from marginalized populations of drug users, sex workers, and homeless persons in Tijuana, Mexico. Six confirmed cases of pandemic (H1N1) 2009 were detected, and the use of rapid, mobile influenza testing was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Research in response to the 2003 SARS outbreak and its impact on people who are homeless identified challenges in communicating public health messages with marginalized populations and in providing space for screening or quarantining ( Leung, 2008 ). Another report identified low incidence of H1N1 among marginalized populations such as sex workers; its authors suggested that social marginalization may have had a protective effect against infection ( Rodwell et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research in response to the 2003 SARS outbreak and its impact on people who are homeless identified challenges in communicating public health messages with marginalized populations and in providing space for screening or quarantining ( Leung, 2008 ). Another report identified low incidence of H1N1 among marginalized populations such as sex workers; its authors suggested that social marginalization may have had a protective effect against infection ( Rodwell et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among the homeless people included during the 2011 snapshot, the rate of seasonal influenza vaccination was reported as 35.6% (data not shown), which was lower than the estimated influenza vaccination coverage in persons aged less than 65 years with an underlying condition in France in January 2011 (46.6%) [ 12 ]. Recently, a study suggested that the social isolation of homeless people might have been protective against pandemic influenza 2009 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the prevalence and transmission of influenza and other respiratory viruses among homeless populations are currently poorly studied [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four PCR-based prevalence surveys conducted among 1103 homeless or persons from marginalised populations between 2005 and 2018 fulfilled the eligibility criteria [2, 15, 84, 85]. Three were conducted among adult sheltered homeless persons in Marseille, France, and one was conducted among marginalised populations, including homeless persons, in Tijuana, Mexico.…”
Section: Resultsmentioning
confidence: 99%
“…Three were conducted among adult sheltered homeless persons in Marseille, France, and one was conducted among marginalised populations, including homeless persons, in Tijuana, Mexico. Three studies were conducted in adults (mean age: 35-44 years, range 18-84 years) [2, 15, 84] and one in a population comprising children and adults (mean age: 41 years, range 7-76 years) [85]. These studies reported a 1.0-3.0% rate of influenza nasopharyngeal carriage among sheltered homeless persons.…”
Section: Resultsmentioning
confidence: 99%